Pemahaman Gen Z terhadap Testimoni Digital dalam Storytelling Instagram - Farhan, Muhamad; Achmad, Ardan; Putri, Citra Eka (Jurnal Cyber PR, 2025)
This study aims to analyze Generation Z’s perceptions of digital testimonials used in Nee’s Coffee’s Instagram storytelling strategy. As a generation that is highly immersed in social media, Generation Z tends to prioritize authenticity, emotional closeness, and the real experiences of other users when evaluating a brand. Unlike previous studies that primarily emphasize the role of influencers or paid advertising in shaping audience trust on social media, this study specifically highlights how digital testimonials based on authentic user experiences, presented through Instagram storytelling, shape Generation Z’s understanding and perceptions of brand credibility. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with the owner, employees, and Generation Z consumers, supported by observations of Instagram content and documentation of digital activities. The findings indicate that digital testimonials conveyed through Instagram storytelling play an important role in shaping Generation Z’s positive perceptions of brand credibility, emotional appeal, and consumption experience. Testimonials that are authentic, use personal language, and are supported by visual narratives are perceived as more convincing and relevant. In addition, user-generated content encourages the formation of digital word-of-mouth communication and increases audience engagement. This study confirms that digital testimonials within social media storytelling represent an effective communication strategy for reaching and building relationships with Generation Z.